The Crime of Marriage: Arbella Stuart and The Duchess of Malfi - Steen, Sara Jayne (The sixteenth century journal, 1991)
Many historical critics contend that Jacobean audiences, unlike modern audiences, would have condemned the Duchess of Malfi's marriage. Because the circumstances surrounding the marriage of the Lady Arbella Stuart parallel those of John Webster's Duchess, contemporary responses to Stuart's case may be the best available clues to the sentiments current when The Duchess of Malfi first was performed. Extant reactions to Stuart's marriage suggest that "what Jacobeans believed" was ideologically diverse: some people indeed criticized Stuart's actions, but others were sympathetic to and even supportive of what they perceived as a romantic match - which suggests that not all playgoers entered the Blackfriars theater predisposed to judge the Duchess harshly.